Effects of Transient and Nontransient Changes of Surface Feature on Object Correspondence. (April 2020) - Jiang, Hao
Object correspondence is a fundamental problem in perception. Classic theories hold that the computation of correspondence is solely based on spatiotemporal information. Recent research showed that surface features also play an important role. However, the surface features of objects in many studies did not change throughout a trial. This study investigated the effect of feature change on object correspondence using the object-reviewing paradigm. Two moving objects underwent transient feature changes on color dimension (Experiment 1A) or a combination of three dimensions (Experiment 2A). Moreover, the objects moved behind four occluders to make the feature change nontransient (Experiments 1B and 2B). Object-specific preview benefits were reduced or eliminated when feature changes were transient, but the benefits were not affected when feature changes were nontransient. The effects of transient versus nontransient changes of surface feature in object correspondence are discussed.